(untitled) (Journal of Academic Research, 2024)
Arbitration is considered an essential tool for settling commercial and civil disputes, as it provides a quick and effective alternative to traditional litigation. The arbitration system in Libya was updated by Law No. 10 of 2023, which reflects the state’s efforts to develop the system in line with international standards, and after years of work to improve it since 2008-2009. The update includes aspects such as writing in arbitration documents, the independence of the arbitration contract, and recognition of electronic arbitration. The research addressed the subject from the perspective of how international commercial arbitration deals with conflict of laws issues, in light of the increasing international disputes and the complexity of legislation. Thus, the research aims to analyze the role of arbitration in addressing conflict of laws issues from the perspective of legitimacy and legality, and to evaluate the effectiveness of the new Libyan law in this context. The approach is based on a descriptive analytical study to provide a comprehensive vision of arbitration’s ability to overcome these problems. The results indicated that the researcher reached that international commercial arbitration is an effective means of settling cross-border disputes, which enhances confidence and speeds up procedures. It is also compatible with Islamic law and positive laws, which ensures the legitimacy of arbitrators’ decisions. However, the research indicates the need to enhance legal awareness, improve the legislative framework for international commercial arbitration, join relevant international agreements, and develop oversight mechanisms to ensure fairness and credibility in the arbitration system.